Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I've been asked to prove this inequaltiy $$\dfrac{(x+y)^{1/2}+(x+z)^{1/2}+(y+z)^{1/2}}{\sqrt{(x+y+z)}}<=\sqrt{6}$$

$x, y, z$ are real numbers, $x + y + z\neq 0$

Every time I try the result is nothing.

I appreciate writing proof, but the hint or showing the road(first step) is huge help.

Thank you.

share|cite|improve this question
This does not hold. For $x=y=z=10^{-100}$ the left hand side is $\approx 10^{50}$, for $x=y=z=10^{100}$ it is $\approx 10^{-50}$. – Hagen von Eitzen Feb 11 '13 at 15:05
@amWhy You kept the wrong inequality. – Did Feb 11 '13 at 15:06
Did I edit this correctly? – amWhy Feb 11 '13 at 15:06
Sorry, both are wrong for homogeneity reasons... Maybe a square root in the denominator as well? – Did Feb 11 '13 at 15:08
I was looking at the title: the x, y, z at the end in the body were part of $x, y, z$ are real numbers. Title: "((x+y)^.5 +(x+z)^.5+(y+z)^.5)/(x+y+z)>(6^.5) for every Real x, y, z" – amWhy Feb 11 '13 at 15:08
up vote 2 down vote accepted

Let $a=\sqrt{x+y}$, $b=\sqrt{y+z}$, $c=\sqrt{x+z}$. Then you want to show $$\frac{\sqrt{x+y}+\sqrt{x+z}+\sqrt{y+z}}{3}=\frac{a+b+c}3\le \sqrt{\frac{a^2+b^2+c^2}3}=\sqrt{\frac{2(x+y+z)}{3}},$$ which is just the inequality between arithmetic and quadratic mean.

Remark: In the inequality between arithmetic and quadratic mean, we have equality iff $a=b=c$, hence iff $x=y=z$.

share|cite|improve this answer

For the record, the inequality to prove might be $$ \sqrt{x+y}+\sqrt{y+z}+\sqrt{z+x}\leqslant\sqrt{6}\cdot\sqrt{x+y+z}, $$ for nonnegative $x$, $y$ and $z$.

To prove this, note that the function $u:a\mapsto\sqrt{a}$ is concave on $a\geqslant0$ hence, for every nonnegative $a$, $b$, $c$, $$ \frac{u(a)+u(b)+u(c)}3\leqslant u\left(\frac{a+b+c}3\right), $$ and apply this inequality to $a=y+z$, $b=z+x$, $c=x+y$.

share|cite|improve this answer
you should metion and provide reference to the inequality Jensen's inequality you are using. – achille hui Feb 11 '13 at 15:47
@achillehui Should I? – Did Feb 13 '13 at 17:40
you should at least mention the name of inequality you are using. When OP encounter similar problem, he/she will hopefully know what to do (instead of asking same question here). – achille hui Feb 13 '13 at 18:16

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.